PEMIKIRAN ABU NASR MUHAMMAD AL-FARABI TENTANG NILAI-NILAI PENDIDIKAN KEPEMIMPINAN NEGARA UTAMA - Khoiruddin, Ahmad Rijal (Universitas Muhammadiyah Surakarta, 2017)
There are two essential components in state management those are the absolute existence of leaders and its society. The quality of leaders in a state is based on the quality of its society education. Due the process of education that takes place on the scope of society becomes a decisive factor both the poor and good leaders who lead a state. This leadership discourse became the main point to be a subject in theme of Indonesian educational society in this era. Acts of corruption, collusion, nepotism of leadership oligarchy and public apathy can be referred to the condition and quality of leadership education in that society. One of the most prominent Islamic figures in state politics studies is Abū Naṣr Muḥammad bin Muḥammad al-Fārābī. Al-Fārābī is a political philosopher and Islamic scholar who has formulated the concept of the perfect state and its leadership concept known as al-Madīnah al-Fāḍilah. According to al-Fārābī a leader is required to provide the education service to his community and lead them to achieve mutual happiness. The problem formulation of this research is how al-Fārāb's idea about the concept of leadership of the perfect state and its application in Islamic education. The goal of al-Fārābi's leadership education is divided into two kinds, those are to form a leader's character and equip the society with theoretical discourse of leadership. The purpose of this study is to examine al-Fārāb's idea about the concept of leadership of the perfect state, then apply the values of leadership education in Islamic religious education, in this case on Islamic education subject in MTs (Islamic Junior High School) and MA (Islamic Senior High School). The values of al-Fārābi's educational leadership are summarized into three, faith to Allah only (tauhīd), cooperation (ta'āwun) and noble character (al-akhlāk al-karīmah). This research based on literature that gain qualitative method. It used a philosophical and political approach, to examine al-Fārābī’s thought in philosophical and political state. Documentation method was used to collect the information by analyzing the content of obtained information. The results proved that in general the material of Islamic religion in the level of Mts and MA only contains the values or principles of monotheism, noble character or morality and alias. From the analysis it can be understood that the Islamic religious lesson printed is not perfect or comprehensive, because the discussion does not includes on various aspects, especially in terms of leadership, which is a big problem in Indonesia today. The solution of the problem is to add the values of al-Farabi's leadership education to lesson in the books of Islamic religious education. The concept of al-Farabi's leadership is a form of integration between the principles of faith to Allah only and philosophy. This means philosophically, the concept of leadership can be applied to the subject matter of Islamic religion. So that learners will get additional scientific treasures about leadership, which later expected to be able to become leaders of quality and can contribute in solving leadership problems and society in Indonesia.Dalam kepengurusan suatu negara terdapat dua komponen penting yang mutlak keberadaannya yaitu pemimpin dan masyarakat yang dipimpin. Kualitas pemimpin negara dipengaruhi oleh kualitas pendidikan masyarakat tersebut. Sehingga proses pendidikan yang berlangsung pada lingkup masyarakat menjadi faktor penentu baik buruknya pemimpin yang memimpin suatu negara. Wacana kepemimpinan ini menjadi poin utama untuk dijadikan subjek dalam tema pendidikan masyarakat Indonesia era ini. Tindak korupsi, kolusi, nepotisme oligarki kepemimpinan dan sikap apatis masyarakat dapat dirujuk atau berawal dari kondisi dan kualitas pendidikan kepemimpinan dalam masyarakat itu. Salah satu tokoh Islam yang konsen dalam hal politik kenegaraan adalah Abū Naṣr Muḥammad bin Muḥammad al-Fārābī. Al-Fārābī merupakan seorang filosof politik dan ulama Islam yang telah merumuskan konsep negara yang ideal beserta kepemimpinannya yang dikenal dengan al-Madīnah al-Fāḍilah. Menurut al-Fārābī seorang pemimpin dituntut bisa memberikan pendidikan kepada masyarakatnya dan membawa mereka meraih kebahagiaan bersama. Rumusan masalah dari penelitian ini adalah bagaimana konsep kepemimpinan negara utama al-Fārābī dan aplikasinya dalam pendidikan agama Islam. Tujuan dari penelitian ini adalah mengkaji pemikiran al-Fārābī tentang konsep kepemimpinan negara utama, kemudian mengaplikasikan nilai-nilai pendidikan kepemimpinannya dalam materi pelajaran pendidikan agama Islam jenjang MTs dan MA. Nilai-nilai pendidikan kepemimpinan al-Fārābī terangkum menjadi tiga, yaitu keimanan (tauhīd), kerjasama (ta’āwun) dan akhlak mulia (al-akhlāk al-karīmah). Penelitian ini bersifat kepustakaan (library research) dengan menggunakan metode kualitatif. Pendekatan yang digunakan adalah pendekatan filosofis dan politik, untuk mengkaji pemikiran filsafat dan politik kenegaraan al-Fārābī. Metode pengumpulan data menggunakan metode dokumentasi dengan menganalisis isi (content analysis) dari data-data yang diperoleh. Hasil penelitian menunjukkan bahwa secara umum materi-materi pelajaran agama Islam pada jenjang Mts dan MA hanya memuat nilai-nilai atau prinsip-prinsip tauhid, sifat-sifat atau akhlak mulia dan ketaladanan. Dari analisis tersebut dapat dipahami bahwa materi pelajaran agama Islam yang tercetak dalam buku pelajaran kurang sempurna atau komperhensif, karena pembahasannya tidak menyinggung berbagai macam aspek, khususnya dalam hal kepemimpinan, yang menjadi masalah besar di Indonesia saat ini. Solusi dari masalah tersebut adalah dengan menambahkan pada setiap materi pelajaran dengan nilai-nilai pendidikan kepemimpinan al-Farabi. Konsep kepemimpinan al-Farabi ini merupakan bentuk integrasi antara prinsip-prinsip tauhid dan filsafat. Artinya secara filosofis konsep kepemimpinannya dapat diaplikasikan ke dalam materi pelajaran agama Islam. Sehingga peserta didik akan mendapatkan khazanah keilmuan tambahan mengenai kepemimpinan, yang nantinya diharapkan mampu untuk menjadi pemimpin-pemimpin yang berkualitas serta dapat berkontribusi dalam menyelesaikan masalah kepemimpinan dan tatanan masyarakat di Indonesia.